Submicrometer-sized Pickering emulsions stabilized by silica nanoparticles with adsorbed oleic acid - Sadeghpour, Amin (Langmuir : the ACS journal of surfaces and colloids, 2013)
Oil-water Pickering emulsions of about 200 nm were stabilized by nanosized hydrophilic silica after a simple surface treatment method. We have modified the aqueous silica nanoparticle dispersions by simple adsorption of oleic acid to their surfaces, improving the hydrophobicity of the particles while maintaining their charge and stability. The adsorption was monitored by small-angle X-ray scattering and electrophoretic measurements to estimate the interparticle interactions and surface charges. The effect of various parameters, such as nanoparticle concentration, amount of oleic acid, ionic strength, and pH, on the droplets' size and stability was investigated by dynamic light scattering. Furthermore, the ability of these modified silica nanoparticles to stabilize long-chain alkanes, liquid paraffin, and liquid-crystalline phases was examined